2022
DOI: 10.21608/ejoh.2022.137167.1198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shoots and Clusters Density on Microclimatic Changes, Yield, and Fruit Quality of King Ruby Grapevines

Abstract: T HE fruit quality of grapevines is a great importance for local consumption and export.Shoots and clusters thinning are substantial agricultural practices in grapevines to improve the berries quality. Herein, 10-years-old King Ruby grapevines were examined in two successive seasons. Four different levels of shoots number were applied (48, 42, 36, and 30, shoots/vine) with two different levels of clusters (30 and 24 clusters per vine). Results showed that the gradual decrease of shoots and clusters/vine impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The effectiveness of cluster thinning increased when combined with pinching. The results of our study came on line with that reported by Myriathouses (1966), James et al (1983, Dokoozlian and Hirschfelt (1995), Gamerol et al (2014), Abd-El-Wahab (2006, Prajitna et al (2007), Reynolds et al (2007), Rathea et al (2011), Fazekas et al (2012, Matteo Gatti et al (2012), Nurhan Keskin et al (2013), El-Kenawy ( 2018) Bassiony (2020) and El-Kenawy (2022) Girdling executed by cutting out a thin strip of bark from around the trunk or arms by using a special knife. This practice interrupts the flow of carbohydrates down making more food available for the fruit.…”
Section: Discussionsupporting
confidence: 90%
“…The effectiveness of cluster thinning increased when combined with pinching. The results of our study came on line with that reported by Myriathouses (1966), James et al (1983, Dokoozlian and Hirschfelt (1995), Gamerol et al (2014), Abd-El-Wahab (2006, Prajitna et al (2007), Reynolds et al (2007), Rathea et al (2011), Fazekas et al (2012, Matteo Gatti et al (2012), Nurhan Keskin et al (2013), El-Kenawy ( 2018) Bassiony (2020) and El-Kenawy (2022) Girdling executed by cutting out a thin strip of bark from around the trunk or arms by using a special knife. This practice interrupts the flow of carbohydrates down making more food available for the fruit.…”
Section: Discussionsupporting
confidence: 90%